Dilatory and downward development of 3‐m scale Irregularities in the funnel‐like region of a rapidly rising equatorial plasma bubble - Tulasiram, S.; Ajith, K. K.; Yokoyama, T.; Yamamoto, M.; Hozumi, K.; Shiokawa, K.; Otsuka, Y.; Li, G. (My University, 2020)
The equatorial plasma bubbles, once developed, grow nonlinearly into topside ionosphere, and simultaneous secondary instabilities lead to the development of shorter scale irregularities. The altitudinal growth and generation of smaller scale irregularities determine the spatio‐temporal occurrence and the intensity of ionospheric scintillations at wide spectrum of radio waves and have significant implications on the GNSS/Satellite Based Augmentation Systems. In this letter, we present a unique equatorial plasma bubble observation from equatorial atmosphere radar that provides hitherto undisclosed evidence for the smaller (3‐m) scale irregularities initially developing at higher altitudes and subsequently developing to lower altitudes in a narrow funnel‐like structure. The responsible mechanisms for early development of shorter scale irregularities in the topside and their subsequent development at lower altitudes are discussed in light of difference between the time scales of altitudinal growth and cascading rate of secondary instabilities through high‐resolution bubble model simulations.
Keywords: Equatorial Plasma bubble; EPBs